2009
DOI: 10.1097/ccm.0b013e3181958c81
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative volume replacement in children undergoing cardiac surgery: Albumin versus hydroxyethyl starch 130/0.4*

Abstract: In children undergoing cardiac surgery, 6% HES 130/0.4 may represent an interesting alternative to 4% albumin for intraoperative fluid volume replacement because of its lower cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 26 publications
9
56
0
Order By: Relevance
“…These latter results were confirmed in a meta-analysis (Martin, Jacob et al, 2013). These two formal analyses are in accordance with the results of two prospective randomized controlled studies performed in children undergoing cardiac surgery, that reported the equivalence of tetrastarches compared to human albumin for perioperative fluid replacement, without any increase in the incidence of postoperative complications (Hanart, Khalife et al, 2009;Van der Linden, De Ville et al, 2013). In these studies, the tetrastarch was associated with a decreased fluid balance, which could have a significant impact on postoperative morbidity and mortality (Hassinger, Wald et al, 2014).…”
Section: Levi Department Of Medicine Academic Medical Centre Unisupporting
confidence: 74%
“…These latter results were confirmed in a meta-analysis (Martin, Jacob et al, 2013). These two formal analyses are in accordance with the results of two prospective randomized controlled studies performed in children undergoing cardiac surgery, that reported the equivalence of tetrastarches compared to human albumin for perioperative fluid replacement, without any increase in the incidence of postoperative complications (Hanart, Khalife et al, 2009;Van der Linden, De Ville et al, 2013). In these studies, the tetrastarch was associated with a decreased fluid balance, which could have a significant impact on postoperative morbidity and mortality (Hassinger, Wald et al, 2014).…”
Section: Levi Department Of Medicine Academic Medical Centre Unisupporting
confidence: 74%
“…13 However, the latter study had some limitations: it was single center, not double blinded; all patients received aprotinin that has been since withdrawn from the market; and most of the observations were limited to the first 24 h after surgery. In addition, a 4% albumin solution was used, which is slightly hypooncotic.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Standl et al (2008) [7] comparable volumes of 6% HES 130/0.4 and 5% human albumin were infused in 82 small infants (<2 years) undergoing non-cardiac surgery to restore or maintain hemodynamic stabilization. Hanart et al (2009) [8] compared the effects of 6% HES 130/0.4 and 4% human albumin on perioperative blood loss and intraoperative volume requirements in 119 pediatric patients undergoing cardiac surgery. Both groups received comparable high volumes of both colloids (50 ml/kg), and measured or calculated blood losses were similar between both groups.…”
Section: Discussionmentioning
confidence: 99%